Design and Reliability Analysis of Four-Legged Jacket Type Oï¬€shore Platform in North Java Sea - Kaban, Siti; Herho, Sandy Hardian Susanto; Tawekal, Ricky; Irawan, Dasapta Erwin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
In ideal conditions, offshore platform design follows standardized international criteria such as the American Petroleum Institute Recommended Practice 2A-LRFD (API RP2A-LRFD) to ensure structural reliability and safety. However, the real conditions in the Java Sea present unique challenges, as environmental loading patterns and regional factors may differ from those assumed in global standards. This study proposes a comprehensive solution through combined structural analysis and reliability assessment using Monte Carlo simulation methods. The urgency of this research stems from the critical need to validate and potentially adjust design standards for regional applications, ensuring the long-term safety and reliability of offshore structures in Southeast Asian waters. The research objectives focus on evaluating the structural reliability of a four-legged jacket type platform using both deterministic and probabilistic approaches, specifically assessing the applicability of API RP2A-LRFD criteria to Java Sea conditions. Results demonstrate that while the structure meets basic design criteria, the reliability indices (Î² = 16.70 for LRFD, Î² = 22.29 for unfactored) suggest current load factors may be overly conservative for regional conditions.